Impact of COVID-19 on the Participation of Iranian Adolescents in Daily Life: Development and Validation of the IAPAT-C Tool - Ghodsiyeh Joveini; Laleh Lajevardi; Mitra Khalafbeigi; Afsoon Hasani Mehraban; Armin Zareiyan (Occupational Therapy International)
Conclusion: The electronic version of the IAPAT-C was valid and reliable. COVID-19 significantly affected various aspects of Iranian adolescents’ daily lives. Accordingly, it is necessary to provide appropriate interventions and policies for this sensitive class.